2021
DOI: 10.3390/polym13071110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adding Antioxidants on the Lightfastness Improvement of Refined Oriental Lacquer

Abstract: Refined oriental lacquer (ROL) is a natural polymeric material with a satiny texture, elegant beauty, and high durability for wood furniture and handicraft finishing. However, its poor lightfastness, which results from the photo-degradation or photo-oxidation of its main component, catechol derivatives, must be improved for its widespread utilization. In this study, two experiments were performed. First, five types of antioxidants, including three primary antioxidants, such as 2,2′-methylenebis(6-nonyl-p-creso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The thermogravimetric diagrams (TGA) and derivative thermogravimetric diagrams (DTG) of ROL films with various A. confusa heartwood extractive additions are displayed in Figure 8 and Figure 9 , respectively. The DTG curves showed that the thermal degradation of ROL film consisted of three main steps; the first step occurred at 60–200 °C, representing the decomposition of the compounds with low molecular weight and water vaporization; the second step occurred at around 200–350 °C, corresponding to the degradation of the side chain end groups of alkylcatechols and alkenylcatechols; the third step occurred at around 350–550 °C, indicating the fragmentation of benzene ring-side chain bonding (-C-O-Ar) of the network structure of ROL film [ 1 , 6 , 21 ]. Gaugler and Grigsby [ 70 ] reported that the thermal decomposition of condensed tannins from pine bark was suggested at 280 °C and 450 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermogravimetric diagrams (TGA) and derivative thermogravimetric diagrams (DTG) of ROL films with various A. confusa heartwood extractive additions are displayed in Figure 8 and Figure 9 , respectively. The DTG curves showed that the thermal degradation of ROL film consisted of three main steps; the first step occurred at 60–200 °C, representing the decomposition of the compounds with low molecular weight and water vaporization; the second step occurred at around 200–350 °C, corresponding to the degradation of the side chain end groups of alkylcatechols and alkenylcatechols; the third step occurred at around 350–550 °C, indicating the fragmentation of benzene ring-side chain bonding (-C-O-Ar) of the network structure of ROL film [ 1 , 6 , 21 ]. Gaugler and Grigsby [ 70 ] reported that the thermal decomposition of condensed tannins from pine bark was suggested at 280 °C and 450 °C.…”
Section: Resultsmentioning
confidence: 99%
“…In the report of Hong et al [ 12 ], they mixed the benzotriazole UV absorber and HALS with OL for enhancing lightfastness. In the earlier documents [ 13 , 14 , 19 , 20 , 21 ], the effects of UV screener (titanium dioxide), different types of HALS, and antioxidants on the lightfastness of ROL had been examined. However, many photostabilizers are synthetic and petrol-based compounds, which are potentially harmful to human health and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we UV absorbers themselves can absorb incident UV radiation and convert it into benign thermal energy with no environmental impairment. Their working mechanism entails excited-state intramolecular proton transfer facilitated by UV irradiation, which cleaves the closed-shell intramolecular hydrogen bonds and generates unstable ketonic forms that relax to the ground state with photoenergy dissipated as heat, thereby alleviating UV-induced effects on the material system and decelerating yellowing [28][29][30]. Currently, common UV absorbers are added to polyurethane emulsions through physical blending, a method that not only requires a high concentration of UV absorbers, reaching 1 g/100 mL, but also has a significant impact on the stability of the emulsion.…”
Section: Introductionmentioning
confidence: 99%
“…It is a kind of water-in-oil reactive bio-based composite system. 24,25 Lacquer phenol is the main film-forming substance of oriental lacquer, which has a direct impact on the quality and film-forming properties. Lacquer phenols are polyphenolic compounds containing double bonds with multiple reactive centers.…”
Section: Introductionmentioning
confidence: 99%